PENCEGAHAN KECURANGAN: APAKAH WHISTLEBLOWING SYSTEM, PENGENDALIAN INTERNAL, GOOD CORPORATE GOVERNANCE, DAN INTEGRITAS PENTING? - Aryani, Aryani; Fitri, Fauziah Aida (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2023)
This study examines the effect of the whistleblowing system, internal control, Good Corporate Governance, and integrity on fraud prevention. The population in this study were all internal employees of the Aceh Province Directorate General of Taxes. The sampling technique is saturated sampling or census with 108 respondents. The data type used is primary data obtained through distributing questionnaires directly to the respondents. This study uses multiple linear regression analysis with the help of the IBM SPSS Statistics 25 program. The findings indicate that the whistleblowing system does not affect fraud prevention. Internal control does not affect fraud prevention. Good Corporate Governance has a positive and significant effect on fraud prevention. Integrity has a positive and significant effect on fraud prevention. These results are expected to be a point of view for the Aceh Province Directorate General of Taxes in preventing fraud.